Push Characteristics in Wheelchair Court Sport Sprinting. (2016) - van der Slikke, Rienk; Berger, Monique; Bregman, Daan; Veeger, DirkJan
Abstract: Short sprints are important components of most wheelchair court sports, since being faster than the opponent often determines keeping ball possession or not. Sprinting capacity is best measured during a field test, allowing the athlete to freely choose push strategies adapted to their own wheelchair setting, physical ability, classification and speed changes during a sprint. The key test outcome is sprint duration, but there are various ways to accomplish the same sprint time. So can different push strategies be identified in a wheelchair sport and how do they relate to athlete level/classification and wheelchair configuration? These relationships were investigated by field tests of 30 male wheelchair basketball athletes during a 12 meter sprint in their own wheelchair. A recently developed method for ambulatory measurement was used to calculate wheelchair kinematics[1], providing outcomes on displacement, speed, acceleration and pushes. Additionally maximal isometric push force was recorded and rear seat height was noted. Within the measured athletes, internationals were expected to be faster due to a better physical training status and technique, allowing them to sprint with fewer (but more powerful) pushes. Likewise, athletes of higher classification were expected to be faster due their superior physical capacity, but the effect on the number of pushes used was not that evident. Video analysis was added to validate push detection of the ambulatory measurement system. Mutual correlations and competition level differences of sprint characteristics were calculated. General Linear Models (GLM) were drawn to determine the effect of competition level and classification on sprint time and number of pushes. In the overall dataset sprint characteristics did not correlate significantly with classification, but if split by competition level, there were significant correlations with sprint time (r=-0.715, p=0.006) and number of pushes (r=-0.647, p= 0.017) in the national level athletes. Sprint time, number of pushes and isometric push force differed significantly between national and international level wheelchair basketball athletes. Competition level showed to be a significant (p<0.05) factor in univariate GLMs for sprint time and number of pushes, whereas classification did not. The interaction of competition level and classification as a factor in univariate GLMs was significant. As hypothesized, international level athletes were faster with fewer pushes, even though their higher average seat height was less optimal for propulsion[2] . The interaction effect of competition level and classification in the GLM indicates that the effect of classification on sprint time and number of pushes is different between competition levels. Indeed, in the national level athletes there was a clear relationship between classification and sprint time / number of pushes, but not in internationals. This difference is pointing at a more professional level of wheelchair configuration or better technique of the international athletes regarding sprint performance. Given the correlation between seat height and classification, the seat height of lowly classified athletes seemed optimized for sprinting, whereas seat height of highly classified athletes with already adequate sprinting capacity was optimized for upward reach. Future research based on larger groups with more even distribution over classifications could provide more solid models and reveal more detailed insight in push strategy efficacy. Given the proven reliability of the inertial sensor based method[1] and the proven reliability for push detection in sprinting, this research could well be performed using this easy to use ambulatory method. Although more challenging than well controlled experimental research, the field based setting in this research revealed additional information not only describing the relation between wheelchair setting and performance, but also describing its practical applications if other game demands were taken into account. The results of this approach is believed to assist athletes, coaches and wheelchair experts in decision making concerning wheelchair configuration and athlete training.